2003
DOI: 10.1074/jbc.m210718200
|View full text |Cite
|
Sign up to set email alerts
|

The Production of 53–55-kDa Isoforms Is Not Required for Ratl-Histidine Decarboxylase Activity

Abstract: Post-translational processing of the histamine-producing enzyme, L-histidine decarboxylase (HDC), leads to the formation of multiple carboxyl-truncated isoforms. Nevertheless, it has been widely reported that the mature catalytically active dimer is dependent specifically on the production of carboxyl-truncated 53-55-kDa monomers. Here we use transiently transfected COS-7 cells to study the properties of carboxyl-truncated rat HDC isoforms in the 52-58-kDa size range. Amino acid sequences important for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…On the other hand, only 74-kDa form was detected in lipopolysaccharide-activated mouse macrophages and monomeric IgE-activated immature bone marrow-derived cultured mast cells, in both of which a large increase in histamine synthesis is observed (21,22). Other variants with intermediate sizes (58ϳ64-kDa) have also been reported in the stomach, fetal liver, and testis (18,23,24). These findings have highlighted the complexity in the regulation of enzyme activity and intracellular localization of HDC through the post-translational processing.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, only 74-kDa form was detected in lipopolysaccharide-activated mouse macrophages and monomeric IgE-activated immature bone marrow-derived cultured mast cells, in both of which a large increase in histamine synthesis is observed (21,22). Other variants with intermediate sizes (58ϳ64-kDa) have also been reported in the stomach, fetal liver, and testis (18,23,24). These findings have highlighted the complexity in the regulation of enzyme activity and intracellular localization of HDC through the post-translational processing.…”
mentioning
confidence: 93%
“…C-terminal 20-kDa region mediates the ER-targeting of HDC and the membrane-bound 74-kDa form possesses a lower activity than that of the truncated 54-kDa form in the cytosol. Fleming and Wang (18) demonstrated that rat 74-kDa form expressed in COS-7 cells is cleaved to multiple forms and that formation of the main 55-kDa form is prevented by mutations at the residues, Ser 502 , Lys 503 , and Asp 504 , whereas these mutations had no effects on the enzyme activity. However, this putative processing site was not found in the primary sequence of mouse and human HDC, and no processed forms were detected in COS-7 cells expressing mouse 74-kDa HDC (17).…”
mentioning
confidence: 99%
“…tion occurs at both the transcriptional and post-translational levels, the latter by proteolytic processing through the ubiquitin-proteasome pathway (6,7).…”
mentioning
confidence: 99%
“…Further work will examine which sites were phosphorylated under our conditions as well as the kinetic parameters modified by CaMKII phosphorylation. It is generally accepted that carboxyl-terminal truncation of the full-length protein yields a catalytically active form of M r 55,000, whose properties are matched closely by 1/512 HDC (Taguchi et al, 1984;Joseph et al, 1990;Engel et al, 1996;Olmo et al, 2002;Rodriguez-Caso et al, 2003), although controversy about the size of the functional forms of HDC in vivo still exists (Dartsch et al, 1999;Fleming and Wang, 2003). On the other hand, CaMKII activation of HDC does not seem to require additional proteins, because we can increase its activity in vitro using purified enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…These neurons are characterized by the presence of the en-zyme-synthesizing histamine histidine decarboxylase (HDC). HDC is a pyridoxal-5Ј-phosphate-dependent decarboxylase translated as a 74-kDa precursor that undergoes carboxylterminal truncation to yield the active forms of the enzyme (Joseph et al, 1990;Dartsch et al, 1999;Fleming and Wang, 2003;Rodriguez-Caso et al, 2003). In a previous work, we showed that histamine synthesis can be stimulated by the adenylate cyclase/protein kinase A pathway in nerve endings, an effect that is inhibited by H 3 receptors (GomezRamirez et al, 2002).…”
mentioning
confidence: 99%